Intrathoracic pressure regulation to treat intraoperative hypotension: A phase II pilot study. Issue 6 (June 2015) - Birch, Martin; Kwon, Younghoon; Loushin, Michael K.; Puertas, Laura; Prielipp, Richard; Belani, Kumar; Beebe, David
Abstract : BACKGROUND: Intraoperative hypotension secondary to acute blood loss and fluid shifts increases morbidity and mortality. Intrathoracic pressure regulation (IPR) is a new therapy that enhances circulation by increasing venous return with a negative intrathoracic pressure created noninvasively, either actively (vacuum source or patient inspiration) or passively (chest recoil during cardiopulmonary resuscitation). OBJECTIVE: In this Phase II pilot study, we tested the hypothesis that active IPR therapy would improve the haemodynamic status of patients who developed clinically significant hypotension during abdominal surgery. DESIGN: A phase II, single cohort, interventional pilot study. SETTING: University of Minnesota Fairview Hospital. PATIENTS: Twenty-two patients [American Society of Anesthesiologists (ASA) physical status I to III] were enrolled prospectively of whom 15 experienced intraoperative hypotension. INTERVENTION: If intraoperative hypotension occurred more than 10 min after induction, the IPR device was applied immediately for a minimum of 10 min. MAIN OUTCOME MEASURE: The hypotensive SBP immediately before the start of IPR treatment was compared with the SBP obtained at the end of IPR therapy. The paired Student's t -test was used to determine statistical significance ( P < 0.05). RESULTS: Fifteen of the 22 patients enrolled experienced 18 hypotensive episodes, which were treated with at least 10 min of IPR therapy. Fourteen episodes responded to IPR alone and four episodes (four patients) required additional fluid and vasopressor therapy to treat the hypotension. The group mean ± SD SBPs at the onset of the IPR treatment and at the end of IPR treatment were 90.7 ± 9.7 and 98.4 ± 17.4 mmHg ( P = 0.02), respectively. The maximum SBP reached during the treatment was 105.6 ± 19.6 mmHg. Pulse pressure increased from 36.8 ± 8.5 mmHg immediately before IPR treatment to 41.5 ± 11.1 mmHg ( P = 0.02) at the end of IPR treatment. Mean arterial pressure (MAP) increased from 66.3 ± 9.4 mmHg immediately before IPR treatment to 71.5 ± 14.4 mmHg ( P = 0.03) at the end of IPR treatment. No adverse events were identified with use of the IPR device. CONCLUSION: IPR may be useful in treating intraoperative hypotension without additional fluid or vasopressor therapy. No significant adverse events were observed. On the basis of this phase II pilot study, a larger study is justified.